Evolutionary history of Coleoptera revealed by extensive sampling of genes and species - Zhang, Shao-Qian; Che, Li-Heng; Li, Yun; Dan Liang; Pang, Hong; Ślipiński, Adam; Zhang, Peng (Nature communications, 2018)
Beetles (Coleoptera) are the most diverse and species-rich group of insects, and a robust, time-calibrated phylogeny is fundamental to understanding macroevolutionary processes that underlie their diversity. Here we infer the phylogeny and divergence times of all major lineages of Coleoptera by analyzing 95 protein-coding genes in 373 beetle species, including ~67% of the currently recognized families. The subordinal relationships are strongly supported as Polyphaga (Adephaga (Archostemata, Myxophaga)). The series and superfamilies of Polyphaga are mostly monophyletic. The species-poor Nosodendridae is robustly recovered in a novel position sister to Staphyliniformia, Bostrichiformia, and Cucujiformia. Our divergence time analyses suggest that the crown group of extant beetles occurred ~297 million years ago (Mya) and that ~64% of families originated in the Cretaceous. Most of the herbivorous families experienced a significant increase in diversification rate during the Cretaceous, thus suggesting that the rise of angiosperms in the Cretaceous may have been an ‘evolutionary impetus’ driving the hyperdiversity of herbivorous beetles. The phylogeny of beetles, which represent ~25% of known extant animal species, has been a challenge to resolve. Here, Zhang et al. infer a time-calibrated phylogeny for Coleoptera based on 95 protein-coding genes in 373 species and suggest an association between the hyperdiversification of beetles and the rise of angiosperms.